Modelling and simulation of intelligent collision avoidance based on ship domain. (22nd April 2020) - Li, Weifeng; Yang, Jiaxuan; Gao, Xiaori; Yu, Jiagen
Intelligent collision avoidance systems can increase the safety of ship navigation and reduce the influence of human error. Thus, related technologies are critical to the development of the world's shipping industry. Risk of collision is a central concept in the Convention on International Regulations for Preventing Collision at Sea, 1972 (COLREGs). Collision risk is also a key factor in determining whether a collision avoidance action is required, specifically with regard to intelligent collision avoidance decisions. On the basis of the ship domain proposed by the Fujii, at first, this paper defined the risk of collision index λ, which can be used to measure the risks between owe ship ant the target ships, then, according to the COLREGs, categorised ship encounter types as head-on situation, crossing situation, and overtaking situation, and established the action flow charts of each of these situations, at last, with the permission of Dalian Maritime University, the training ships of Yu Peng and Yu Kun were selected as simulation objects, the paper presents simulations of head-on, crossing and overtaking situations to verify the usability of the proposed models.